Factors associated with psychological health of female nurses in Malaysian government hospitals - Mohd Hanifa, Suzana (2020)
Women's psychological health has become an important issue in the past few decades due to the changes in the workforce demographics and the existence of blurry boundaries between the domains of work and family. However, how a resource-based perspective or favourable conditions influence women's psychological health have received scant attention from researchers. Specifically, this research was carried out to investigate the relationship of schedule control, family-supportive supervision, core self-evaluations, and work-family conflict with nurses' psychological health (i.e., psychological distress and life satisfaction). The study likewise examined whether work-family conflict will have a mediating influence on these relationships. The present quantitative study utilised a correlational research design. A total of 691 female nurses, who, at the time of the survey, were married with at least one child and working on shifts in state hospitals under the Ministry of Health (MOH) in Peninsular Malaysia, were selected using the multistage cluster random sampling. This study utilised six established instruments, namely, the Schedule Control Scale, Family- Supportive Supervisor Behaviour Scale, Work-Family Conflict Scale, Core Self- Evaluations Scale (CSES), The Satisfaction With Life Scale (SWLS), and the General Health Questionnaire (GHQ). Data obtained from the self-administered questionnaires were analysed with structural equation modeling (SEM) using analysis of moment structures (AMOS). This study revealed that core self-evaluations had a significant association with nurses' psychological distress as well as life satisfaction. Furthermore, schedule control was not significantly related to nurses' psychological distress and life satisfaction; whereas, family-supportive supervision emerged as having a significant direct relationship only with life satisfaction. This study likewise found that family-supportive supervision and core self-evaluations had significant associations with nurses' work-family conflict. In addition, work-family conflict only predicted nurses' psychological distress and not their level of life satisfaction. Results also showed that work-family conflict significantly mediated the association of schedule control, family-supportive supervision, and core self-evaluations with nurses' psychological distress. The mediating structural model of work-family conflict contributed 41% to the direct model (33.8%) to explain the variance in nurses' psychological distress. Specifically, work-family conflict partially mediated the association of core self-evaluations with psychological distress; while, work-family conflict was found to have an indirect effect on the link between schedule control and nurses' psychological distress as well as that between family-supportive supervision and psychological distress. However, work-family conflict did not mediate the relationship of schedule control, family-supportive supervision, and core self-evaluations with nurses’ life satisfaction. Generally, this study highlights the importance of core self-evaluations, familysupportive supervision and work-family conflict in influencing nurses' psychological health. The findings of the study also contribute to the body of knowledge, especially on the significant role of personal resources in shaping nurses' psychological health compared to contextual resources. Several prospective training and intervention programs to promote nurses’ psychological health were suggested, including those aimed at enhancing the personal characteristics of nurses, encouraging supervisors to engage in family-supportive behaviour, and promoting the creation of family-supportive work environment for nurses’ well-being.